On the importance of π-π interactions in the structural stability of phycocyanins - Breberina Luka M.; Nikolić Milan R.; Stojanović Srđan Đ.; Zlatović Mario V. (Journal of the Serbian Chemical Society, 2023)
The influences of π-π interactions in phycocyanin proteins and their environmental preferences were analyzed. The observations indicate that the majority of the aromatic residues in phycocyanin proteins are involved in π-π interactions. Phenylalanine (Phe) and tyrosine (Tyr) residues were found to be involved in π–π interactions much more frequently than tryptophan (Trp) or histidine (His). Similarly, the Phe-Phe and Tyr-Tyr π-π interacting pair had the highest frequency of occurrence. In addition to π-π interactions, the aromatic residues also form π-networks in phycocyanins. The π–π interactions are most favourable at the pair distance range of 5.5–7 Å, with a clear preference for T-shaped ring arrangements. Using ab initio calculations, we observed that most of the π-π interactions possess energy from 0 to -10kJ mol-1. Stabilization centres for these proteins showed that all residues found in π-π interactions are important in locating one or more such centres. Π-π interacting residues are evolutionary conserved. The results obtained from this study will be beneficial in further understanding the structural stability and eventual development of protein engineering of phycocyanins.